SINONIM DAN ANTONIM DALAM BAHASA NIAS UTARA DIALEK BARAT DI DESA ONOLIMBU YÖU KECAMATAN MANDREHE BARAT KABUPATEN NIAS BARAT - Julita Winta Sari Gulo (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was motivated by the use of synonymous and antonymous word in the west dialect of the North Nias language in Onolimbu You village. This research aims to 1) describe the use of synonymous verbs (synonims with the same meaning and almost the same meaning) in the west dialect of the North Nias language in Onolimbu You village, West Mandrehe District, West Nias Regency and 2) describe of the use of the west dialect of the North Nias language verb antonymous in Onolimbu You village, West Mandrehe District, West Nias Regency. This type of research is descriptive qualitative research. The object of this research in the Onolimbu You village community. The research instrument was carried out by researchers. The data collection technique used by researchers is semi-structured interview techniques. The data analysis technique was carried out by following the data collection steps, namely the data reduction stage, the data presentation stage and the data verification stage. Checking the validity of the data used by researchers technique triangulation and source triangulation. The results of the research show that there are synonymous and antonymous verb in Onolimbu You village. There are two types of synonymous verb, namely synonymous with the same meaning and synonyms with almost the same meaning. The suggestions put forward by researchers are 1) for students to carry out further research both in the field studied and other fields to develop knowledge of the Nias language, 2) For parents to continue to implement policies for the younger generation so that they continue to preserve the Nias language.